Enrollment Management and Tuition Discounting - Lucie Lapovsky; Loren Loomis Hubbell (Educational Considerations, 2003)
Enrollment management is critical to the success of all colleges and universities, and especially in times when state appropriations are not increasing, the endowment is not producing at historical levels, and gifts are not keeping pace with inflation.